Empowering Self-Directed Mathematics Learning through Artificial Intelligence: An African Perspective - Makonye, Judah P.; Sulisworo, Dwi (Journal of Educational Technology Innovation and Applications, 2025)
`In the evolving educational landscape, self-directed learning (SDL) is gaining momentum as a pivotal approach to personalized education. This paper explores the integration of Artificial Intelligence (AI) to support SDL in mathematics instruction within the African context. Despite systemic challenges in the region's educational infrastructure, AI presents an opportunity to overcome teacher shortages, unequal resource distribution, and varied student learning needs. Through a conceptual framework and literature-supported analysis, we argue that AI-driven learning environments can significantly enhance learners' autonomy and performance in mathematics. Results from secondary data and expert interviews are presented in two analytical subsections, highlighting opportunities and challenges of AI integration in SDL. The article concludes with practical recommendations for policymakers and educators.